Factors influencing maternal-fetal attachment in adolescent pregnant women: scoping review - Astika, Astika; Suryaningsih, Endang Koni; Anjarwati, Anjarwati (Poltekkes Kemenkes Bandung, 2026)
Background: During pregnancy, one important aspect that needs to be considered is the formation of maternal-fetal attachment (MFA), which is the emotional bond that forms between a mother and her fetus during pregnancy. Maternal-fetal attachment begins to develop before the baby is born, even while it is still in the womb. Objective: This study analyses scientific evidence related to factors that influence maternal-fetal attachment in adolescent pregnant women. Methods: This review used the PRISMA-ScR diagram. Literature searches were conducted using three databases and one search engine, namely PubMed, ScienceDirect, Wiley Online Library, and Google Scholar. This review began in February 2025. Articles were assessed using the Critical Appraisal Skills Programme (CASP) checklist for cohort, cross-sectional, and qualitative studies, with inclusion criteria being original research articles, articles published between 2020-2025, in English, open access and available in full text, with a research focus on MFA in adolescent pregnancy, while exclusion criteria were paid articles and articles with only abstracts. From the 211 articles selected, 7 relevant articles were obtained, 6 quantitative articles and 1 qualitative article. Results: the factors that influence maternal-fetal attachment in adolescent pregnant women are health practices during pregnancy, the mother's psychological condition, emotional and social support, sociodemographic and marital factors, pregnancy characteristics, and family and cultural background. Conclusion: Maternal-fetal attachment in adolescent pregnancy is influenced by psychological, social, and contextual factors. Strengthening psychosocial support and promoting healthy behaviors are essential to improve attachment and maternal well-being.